2021
DOI: 10.1155/2021/1713496
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Changes in Brain Hemodynamics in Patients with Parkinson’s Disease and Risk Factors for Cerebrovascular Disease: A Pilot Study

Abstract: Recent epidemiological studies have revealed a correlation between atypical features and worse functional outcomes in Parkinson’s disease (PD) patients with cerebrovascular disease (CVD). We aimed to evaluate the brain hemodynamics of PD patients with risk factors for CVD using Doppler ultrasonography. In this prospective pilot study, we randomly included 27 outpatients diagnosed with PD. Transcranial color-coded sonography (TCCS) examinations were performed, obtaining measurements of middle cerebral artery me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Other published papers found that patients with vascular risk factors are also more prone to rapid deterioration and increased mortality [9,10,18]. In accordance with a previous study, the presence of two or more vascular risk factors is associated with worse motor impairment, as well as cognitive decline [5,18].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Other published papers found that patients with vascular risk factors are also more prone to rapid deterioration and increased mortality [9,10,18]. In accordance with a previous study, the presence of two or more vascular risk factors is associated with worse motor impairment, as well as cognitive decline [5,18].…”
Section: Discussionsupporting
confidence: 85%
“…PD patients may be classified into three different clinical phenotypes: one in which tremor is the predominant manifestation (Tremor-dominant type), another in which the dominant symptom is rigidity (Akinetic-rigid type) and a third phenotype with no predominant motor manifestation (Mixed type) [24]. A previous small study of our research group evidenced an association between these clinical phenotypes of PD and the presence of risk factors for CVD associated with altered cVR found in transcranial Doppler [5]. However, despite this evidence, none of the previous studies correlated MRI findings, cVR sonographic data, PD motor phenotype, or presence of risk factors for CVD in PD patients together.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Apart from bidimensional mode ultrasound, transcranial colorcoded sonography has already been reported in patients with PD. The F I G U R E 2 Correlation between age and temporal bone thickness in females and males changes on cerebral hemodynamics may determine the severity and clinical outcomes of PD (Brisson, de Cássia Leite Fernandes, et al, 2021). Standardized axial imaging of the butterfly-shaped midbrain is performed with the transducer placed at the preauricular site and the patient in a supine position.…”
Section: Discussionmentioning
confidence: 99%
“…Transcranial sonography (TCS) is a neuroimaging technique used to obtain and evaluate images of the cerebral parenchyma in movement disorders through B‐mode and assess the blood flow velocities of the intracranial vessels through Doppler mode (Brisson et al., 2021 ; Monaco et al., 2018 ). This is an ultrasonographic technique used to detect abnormalities in the echogenicity of substantia nigra (SN), thalamus, lenticular nuclei, red nuclei, the continuation of the median raphe nucleus, and ventricular diameters and assesses vascular reactivity (Brisson et al., 2021 ; Monaco et al., 2018 ; Walter et al., 2008 ). The main limitation of TCS is the lack of bone window, which could vary between 5% and 44% of the population, according to Brisson, Santos et al ( 2021 ), depending on various factors, including, sex, age, and ethnicity.…”
Section: Introductionmentioning
confidence: 99%